Implementation Of Corporate Social Responsibility (CSR) Menteng Mitra Afia Hospital In Educating The Public - Henilia Yulita; Koerniawan Hidajat (Ilomata International Journal of Social Science, 2020)
The research focus is on the activities of Menteng Mitra Afia Hospital in educating public health to the context of public health education itself. This research uses a qualitative paradigm, a paradigm that aims to understand a social phenomenon, as a research approach with case study method. The subject of the research is Menteng Mitra Afia Hospital, Jl. Kali Pasir No.9, RW.10, Kb. Sirih, Kec. Menteng, Kota Jakarta Pusat, Jakarta 10340. Object of the research is corporate social responsibility (CSR)and health education. This research answers how the implementation of (CSR) RS. Menteng Mitra Afia educates the public during a new normal co-19 pandemic. The main informant is dr. Enrico Adhitya Rinaldi M.A.R.S, MH, CHRM as the Managing Director of Menteng Mitra Afia Hospital, as well as the founder of PT. Enmedicare International. The result of the research are: The Infection Prevention and Control Training (PPI) was held on September 27, 2019; The BPJS - Day 2020 on Tuesday, February 11, 2020; Inauguration of Central Jakarta DPK-PPNI 2020 on February 5, 2020; and the last was Empirical Implementation of Social Responsibility (CSR) with Webinar on July 11, 2020. The results of the speaker material responses in this webinar show that on average 70% (percent) of the 512 participating webinar communities are very responsive, or very good (SB) assessing the material provided by filling out questionnaires in a form such as a Likert scale.